Probiotic efficiency of Bacillus sp. in Labeo rohita challenged by Aeromonas hydrophila: assessment of stress profile, haemato‐biochemical parameters and immune responses. (10th March 2017) - Nandi, Ankita; Banerjee, Goutam; Dan, Suhas Kumar; Ghosh, Koushik; Ray, Arun Kumar
Abstract: Fish are always susceptible to a wide variety of deadly pathogens which cause a huge loss in aquaculture industries. In this investigation, we have demonstrated the in vivo probiotic efficiency of Bacillus sp. MVF1 (GenBank Acc. No. KP256503) in Labeo rohita challenged with pathogenic strain of Aeromonas hydrophila (MTCC 1739). To check the probiotic potential of the selected bacterial strain, fish were divided into four groups: control, D1, D2 and D3. A total of 100 days (70 days probiotic feeding + 71th day sampling and 28 days challenged test + 29th day sampling) of feeding trial was conducted. To establish the probiotic potential of Bacillus sp. MVF1, certain haematological parameters (haemoglobin, total erythrocyte and leucocyte count), serum biochemical parameters (total protein, albumin and globulin), immune parameters (serum lysozyme and total IgM levels) and hepatic stress profile (malondialdehyde production, superoxide dismutase and catalase activity) have been measured. Our results demonstrated that red blood cell number, white blood cell number and haemoglobin content were much higher in D2 group fish compared to other groups and control fish. Similarly, total protein contents, albumin concentration, globulin concentration, lysozyme activity and IgM production were also recorded to be highest in D2 group fish. This finding clearly indicated the probiotic potential of Bacillus sp. MVF1 in L. rohita . Furthermore, our results also demonstrated that 1 × 10 7 CFU g −1 feed (D2) provides better immunity compared to 1 × 10 5 (D1) and 1 × 10 9 (D3). Due to beneficial effects, the bacterium Bacillus sp. MVF1 might be useful in aquaculture industries to reduce the disease susceptibility.